Association Between Bedtime at Night and Systolic Blood Pressure in Adults in NHANES - Su, Yingjie; Li, Changluo; Long, Yong; He, Liudang; Ding, Ning (Frontiers in Medicine, 2021)
Objectives: This study aimed to explore the association between bedtime at night and systolic blood pressure (SBP) in adults. Methods: We conducted a cross-sectional study composed of 7642 individuals from the National Health and Nutrition Examination Survey (NHANES). Bedtime was defined as the response to the question:“What time do you usually fall asleep on weekdays or workdays?”. SBP was taken using the average of all measured values. Multiple linear regression analyses were done to explore the relationship between bedtime and SBP. Results: The bedtime was changed from categorical variable to continuous variable for data analysis, and a significantly negatively association was identified between bedtime and SBP(β, -0.23 [95%CI, -0.43, -0.02]). With the delay of bedtime, the SBP showed a gradual decrease trend, and it dropped to the lowest at 0am. After 0am, the SBP gradually increased with the delay of sleep time. The stratified analyses showed that in the female group, with the delay of bedtime, the range of SBP decreased more obviously at 0 am. In the 18-45 year group, bedtime had little effect on SBP. Among ≥ 45 years old group, this trend was still the same. In the black group, an obvious downward trend was found at 22pm. Conclusion: With the delay of bedtime, the SBP showed a gradual decrease trend, and it dropped to the lowest at 0am. After 0am, the SBP gradually increased with the delay of sleep time. Bedtime and SBP showed a U-shaped relationship.